Discovery of millihertz ultraviolet quasi-periodic oscillations in Hercules X-1 - Boroson, B; O'Brien, K; Horne, K; Kallman, T; Still, M; Boyd, P; Quaintrell, H; Vrtilek, S (Institute of Physics Publishing, 2000)
Observations of the ultraviolet continuum of the X-ray binary system Her X-1/HZ Herculis with the Space Telescope Imaging Spectrograph on the Hubble Space Telescope (HST) show quasi-periodic oscillations (QPOs) at frequencies of 8 ± 2 and 43 ± 2 mHz, with rms amplitudes of 2% and 4% of the steady flux. Observations with the Keck Telescope confirm the presence of the higher frequency QPO in the optical continuum, with a rms amplitude of 1.6% ± 0.2%. The QPOs are most prominent in the HST data near φ = 0.5 (where φ = 0 is the middle of the X-ray eclipse), suggesting that they arise not in the accretion disk but on the X-ray-heated face of the companion star. We discuss scenarios in which the companion star reprocesses oscillations in the disk which are caused by either Keplerian rotation or a beat frequency between the neutron star spin and Keplerian rotation at some radius in the accretion disk.